Ploidy levels of Dioscorea alata L. germplasm determined by flow cytometry - Obidiegwu, J.E.; Rodríguez, E.; Ene-Obong, E.E.; Loureiro, J.; Muoneke, C.; Santos, C.; Kolesnikova-Allen, M.; Asiedu, Robert (Springer, 2010)
Dioscorea alata L. is a highly important crop, widely distributed in the humid and semi-humid tropics. Flow cytometry was used to determine the ploidy levels of 74 D. alata genotypes collected mainly from West African countries. Sixty three of the genotypes were found to be tetraploid, one was hexaploid and ten were octoploid. The high percentage of tetraploids together with the small percentage of hexaploid individuals and the absence of diploid individuals gives us some more clues on the possible origin of these species. No association between ploidy level and place of cultivation was found for the tested material. The obtained results represent important knowledge for enhancing the breeding methodologies and optimize germplasm management of this species. It also offers further insights to the phylogeny and evolution of Dioscorea species.